‘They are grabbing houses for themselves!’: Occupying 2 de Maio in the fervour of the Portuguese Revolution - Joana Pestana Lages; Saila-Maria Saaristo; Miguel Tomé (Cidades, Comunidades e Território)
Abstract This paper explores the occupation movement that took place during the so-called ‘Ongoing  Revolutionary Process’ (PREC), from 1974 to 1976. We focus on the specific case of the 2 de Maio neighbourhood in Lisbon, where 25 under-construction housing blocks were occupied in May 1974. We juxtapose these occupations with the occupations of council housing dwellings in Lisbon today, linking their characteristics as well as the socio-political context in which they occur. Methodologically the article draws from the notions of radical memory work and community-based, participatory action research. The analysis reveals that the specific traits of the PREC occupation movement, driven by housing precarity and promoted collectively by the dwellers of lower socio-economic classes, played a vital role in the way they have endured through time. Yet, in particular, the response of the state actors, influenced by the specific political context of the PREC, as well as the wide support received by other actors, was fundamental to enable their permanence and subsequent regularisation. This paper contributes to the debates on the potential of occupations to promote access to housing, highlighting the roles that state actors and the political environment play in terms of legitimising occupations.